2020
DOI: 10.1155/2020/5626503
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of OXA-232 Carbapenemase-Producing ST437 Klebsiella pneumoniae in China

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) was epidemic around the world and become a global threat to public health. The most important carbapenem-resistant mechanism is producing carbapenemases, especially Klebsiella pneumoniae carbapenemase (KPC), which is prevalent in the international clonal complex CC11. The high-risk multidrug-resistant CC11 is widespread worldwide, and KPC-producing and (New Delhi metallo) NDM-producing strains had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“… 4 The plasmid pOXA-232 was a non-conjugative plasmid because it could not be transferred through conjugation experiments. 4 , 9 , 28 The plasmid in our experimental strains was similar to plasmids in other studies. 4–7 , 9 , 28 , 29 The conjugation experiment failed to transfer this bla OXA-232 into E. coli , indicating that it was a non highly conjugative plasmid.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 4 The plasmid pOXA-232 was a non-conjugative plasmid because it could not be transferred through conjugation experiments. 4 , 9 , 28 The plasmid in our experimental strains was similar to plasmids in other studies. 4–7 , 9 , 28 , 29 The conjugation experiment failed to transfer this bla OXA-232 into E. coli , indicating that it was a non highly conjugative plasmid.…”
Section: Discussionsupporting
confidence: 84%
“… 4 , 9 , 28 The plasmid in our experimental strains was similar to plasmids in other studies. 4–7 , 9 , 28 , 29 The conjugation experiment failed to transfer this bla OXA-232 into E. coli , indicating that it was a non highly conjugative plasmid. However, we found OXA-232-producing E. coli during the outbreak.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The majority of these showed phenotypic resistance to both meropenem and imipenem (256/280, 91.4%, Figure 1A), explained by the presence of blaOXA-48-like genes, blaNDM genes, and a combination of ESBLs (blaCTX-M-15, blaCTX-M-71, blaSHV-12, blaSHV-13, blaSHV-27, blaSHV-31, blaSHV-41) and inactivation of porins Ompk35/36 [27]. Of the carbapenem-resistant isolates, 80.3% (225/280) carried blaOXA-48-like genes (blaOXA181 and blaOXA232), and 26.7% (75/280) carried blaNDM-1/5, which supports the reported changing trends in carbapenem resistance [25].…”
Section: Resistance Profile and Their Distributionmentioning
confidence: 99%
“…The emergence and spread of carbapenem-resistant Enterobacteriaceae (CRE) has created an escalating global threat with the dissemination of carbapenemase genes. The most common carbapenemase genes include blaKPC, blaNDM, blaVIM, blaIMP, and blaOXA-48-like (1). A nationwide survey conducted in China showed that acquisition of two carbapenemase genes, blaKPC-2 and blaNDM, was responsible for phenotypic resistance in 90% of the CRE strains tested (58 and 32%, respectively) (2).…”
Section: Introductionmentioning
confidence: 99%